Planning with the landscape — landscape as a service? - Clemens, Corinna (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
What will the landscape and the countryside of the future look like? Who will use it and who will value it? From where we are today it is impossible to foresee the answers to these questions. Nonetheless, spatial planning, which in its very essence and function is anticipatory, is duty bound to seek approaches which will allow it successfully to act within, and to interact with, the future landscape. The following text explores one of these potential approaches as it reflects on the possibilities for spatial planning which may be inherent in an approach which interprets the landscape as a “service for service-providers”.